Improved phenolic acid content and bioactivities of Salvia miltiorrhiza hairy roots by genetic manipulation of RAS and CYP98A14. (30th November 2020) - Fu, Rong; Shi, Min; Deng, Changping; Zhang, Yi; Zhang, Xichen; Wang, Yao; Kai, Guoyin
Highlights: Overexpression of RAS increased phenolic acid accumulation in S. miltiorrhiza . Introduction of CYP98A14 elevated phenolic acid content in S. miltiorrhiza . All transgenic lines showed more excellent antioxidant activity than control. Stronger antibacterial activity was detected in transgenic lines than control. Transgenic lines provide phenolic acid resources for food and healthy products. Abstract: Phenolic acids from Salvia miltiorrhiza have been widely used in nutritious, health-promoting products with an increasing demand. In the current study, two biosynthetic genes RAS (rosmarinic acid synthase) and CYP98A14 (a cytochrome P450-dependent monooxygenase) were successfully introduced into S. miltiorrhiza hairy roots. Overexpression of RAS and CYP98A14 resulted in higher content of phenolic acids (up to over 3-fold) in transgenic lines compared to the control. Meanwhile, DPPH results revealed that engineered S. miltiorrhiza hairy roots had stronger antioxidant activities than the control. In addition, phenolic acid crude extracts of the engineered hairy root lines overexpressing RAS or CYP98A14 showed improved antibacterial activities compared to the control lines. Our work exhibits a useful strategy for enhancement of phenolic acid production and bioactivities of S. miltiorrhiza hairy roots by genetic manipulation of RAS and CYP98A14, and also provides a new resource material to obtain active phenolic acids for food and healthy products.